CRISPR-Cas– induced IRF3 and MAVS knockouts in a salmonid cell line disrupt PRR signaling and affect viral replication - van der Wal, Yorick A.; Nordli, Henriette; Akandwanaho, Allan; Greiner-Tollersrud, Linn; Kool, Jaap; Jørgensen, Jorunn B. (Frontiers in Immunology, 2023)
Interferon (IFN) responses are critical in the resolution of viral infections and are actively targeted by many viruses. They also play a role in inducing protective responses after vaccination and have been successfully tested as vaccine adjuvants. IFN responses are well conserved and function very similar in teleosts and mammals. Teleosts have several IFNs, although these are not orthologues of the mammalian IFNs. Like in mammals IFN responses in piscine cells are initiated by intracellular detection of the viral infection by different pattern recognition receptors. Upon the recognition of viral components in infected cells, IFN responses are rapidly induced to combat the infection.However, many viruses may still replicate and be able to inhibit or circumvent the IFN response by different means. By employing CRISPR Cas9 technology we have disrupted proteins that are central for IFN signaling in the salmonid cell line CHSE-214. We successfully generated KO clones for the mitochondrial antiviral signaling protein MAVS, the transcription factors IRF3 and IRF7-1, as well as a double KO for IRF7-1/3 using an optimized protocol for delivery of CRISPR-Cas ribonucleoproteins through nucleofection. We found that MAVS and IRF3 KOs inhibited IFN and IFN-stimulated gene induction after intracellular poly I:C stimulation as determined through gene expression and promoter activation assays. In contrast, the IRF7-1 KO had no a clear effect. This shows that MAVS and IRF3 are essential for initiation of intracellular RNA-induced IFN responses in CHSE-214 cells. To elucidate viral interference with IFN induction pathways the KOs were infected with Salmon alphavirus 3 (SAV3) and infectious pancreatic necrosis virus (IPNV). SAV3 infection in control and IRF7-1 KO cells yielded similar titers and no cytopathic effect, while MAVS and IRF3 Kos presented with severe cytopathic effect and increased titers 6 days after salmon alphavirus 3 infection. In contrast, IPNV yields were reduced in MAVS and IRF3 Kos, suggesting a dependency on interactions between viral proteins and pattern recognition receptor signaling components during viral replication. Aside from more insight in this signaling in salmonids, our results indicate a possible method to increase viral titers in salmonid cells.